Autodistanciamento, autotranscendência e dimensão noético-espiritual: Frankl e o resgate da antropologia filosófica scheleriana. - Bittencourt, Larissa Fernanda (2024)
The present work focuses on the influence of Scheler's philosophical anthropology on the work of Viktor Frankl, specifically regarding how the concept of spirit proposed by Scheler aligns with the concepts of self-distancing and self-transcendence in Franklian existential analysis. It is important to highlight the relevance of this research, considering that the feeling of existential emptiness in human existence is increasingly prevalent in the contemporary scenario. Thus, understanding the concepts of self-transcendence and self-distancing, as well as the nature of human existence, becomes ever more necessary. In Frankl's work, one can find the philosophical contributions that form the foundation of his Logotherapy, with a particular emphasis on phenomenological and existential components. Among the philosophers studied by Frankl, the phenomenologist Max Scheler stands out as one of his main influences. Scheler not only had a significant intellectual impact on Frankl, altering the trajectory of his studies, but also energetically contributed to the understanding of the human being, which is central to Franklian existential analysis. Given this direct connection between the authors, it is worth asking: how does the concept of spiritual dimension arising from Scheler's philosophical anthropology influence the formulation of Viktor Frankl's concepts of self-distancing and self-transcendence? To answer this research question, we conducted exploratory bibliographical research aimed at determining the legacy of Max Scheler's philosophical anthropology in Viktor Frankl's existential analysis, particularly concerning the concepts of self-distancing and self-transcendence. To this end, we aimed to describe Scheler's philosophical anthropology, and the anthropological vision found in Frankl's work, investigating the resonances of the concept of noetic-spiritual dimension and related concepts of human and spirit within Frankl's notions of self-distancing and self-transcendence. The primary works used in the preparation of this dissertation were The Position of Man in the Cosmos by Max Scheler and Human Suffering: Anthropological Foundations of Psychotherapy by Viktor Frankl. From the research conducted, it was possible to elucidate the philosophical foundations of Franklian existential analysis, demonstrating how Schelerian philosophical anthropology and his phenomenology permeate Viktor Frankl's understanding of humanity and the world, culminating in the formulation of the concepts of self-distancing and self-transcendence. Additionally, we gained a deeper understanding of these concepts, highlighting their importance for the well-being and lives of contemporary human beings.